2016
DOI: 10.17352/2455-5495.000006
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis with Polymethylmethacrylate Restores the Response to Hepatitis B Vaccination in Chronic Dialysis Patients: Hypothesized Mechanism of Action

Abstract: Patients undergoing hemodialysis often present with a reduced response to anti-hepatitis B virus (anti-HBV) vaccination. The soluble form of CD40 (sCD40) is elevated in hemodialysis patients and this has been shown to correlate with lack of response to anti-HBV vaccination. Due to its high molecular weight, conventional dialyzers cannot clear sCD40. Previous studies have demonstrated, that dialysis membranes in polymethylmethacrylate (PMMA) can reduce the levels of sCD40. We have studied the effect of dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Regarding changing the modality, Nongnuch and coworkers reported that seroconversion rates for influenza vaccine were not significantly different between HD and HDF therapies, although seroprotection in patients treated with HDF was sustained for longer compared with those treated by HD [ 21 ]. Regarding the change in dialysis membranes, some studies have reported that the use of PMMA dialyzers has the potential to improve the response to vaccine against HBV in HD patients who were treated with PS-type dialyzers and were classified as nonresponders to the vaccine [ 11 , 12 , 16 ]. These reports showed the removal of soluble CD40 sCD40, which can suppress the interaction between T and B cells, as the possible mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding changing the modality, Nongnuch and coworkers reported that seroconversion rates for influenza vaccine were not significantly different between HD and HDF therapies, although seroprotection in patients treated with HDF was sustained for longer compared with those treated by HD [ 21 ]. Regarding the change in dialysis membranes, some studies have reported that the use of PMMA dialyzers has the potential to improve the response to vaccine against HBV in HD patients who were treated with PS-type dialyzers and were classified as nonresponders to the vaccine [ 11 , 12 , 16 ]. These reports showed the removal of soluble CD40 sCD40, which can suppress the interaction between T and B cells, as the possible mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the improvement in the immune response, it was reported that the response to vaccine against hepatitis B virus could be improved in HD patients who were classed as nonresponders previously, when the dialyzer was changed to BK-F, a dialyzer that uses PMMA membrane [ 11 , 12 ]. Furthermore, it was shown that removal of soluble CD40 (sCD40), which plays a role in antibody production and was not removed by the dialyzer using PS membrane, may be related to this improvement [ 11 , 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%